Overexpression of Sugarcane Sucrose Transporter 1 (SoSUT1) Gene Increases Rice Yield - Putri, Cesha Ananda; Soegiharto, Bambang; Dewanti, Parawita (BRIN, 2020)
The growth and development of plants are determined by photosynthesis, which ultimately results in sucrose. Sucrose is synthesized in the source then translocated to all parts of the plant (sink). The translocation process of sucrose from source to sink is controlled by sucrose protein called sucrose transporter. SoSUT1 is a gene that encodes a sucrose transporter 1 (SUT1) protein in sugarcane. Rice transformation with the SoSUT1 causes overexpression SUT, which is expected to increase the translocation of sucrose into the seed of rice plants. This research was conducted by introducing SoSUT1 in rice plants Inpari 14 SS. Transformation using Agrobacterium tumefaciens vector in apical bud explant Indica rice cv. Inpari 14 SS results in 26 events positive rice contains genes SoSUT1. This study aims to elucidate the inheritance of transgene in the next generation and to characterize its effect on the morphology and the yields of a subsequent generation. The study is conducted by planting the seeds of T1 and T2 plants in media containing Hygromycin and using PCR analysis for further analysis. As the results, from 26 events on the T1 plant, only 3 events of T3 plants were confirmed on the T3 plant. The overexpression of the SoSUT1 gene could increase the number of tillers, the number of productive tillers, panicle length, and panicle exit length, also increasing the number of spherical grains, reducing the number of empty grains and increasing the weight of 1000 grains.